Plan estratégico de desarrollo turístico sostenible para la parroquia de San Carlos de las Minas del cantón Zamora, provincia de Zamora Chinchipe - Rojas Chimbo, María Magdalena (2014)
The elaboration of the "Strategic Plan for Sustainable Tourism Development for the parish of San Carlos Mine, province of Zamora Chinchipe" whose purpose is to improve the quality of life of its inhabitants and even provide excellent hospitality to tourists and generate income for the parish. For the realization of this plan we began with the analysis of the actual situation of the parish, which allowed us obtain a clear perspective that facing the sector. Subsequently, the analysis of potential tourist of the parish was made. That includes information about tourism installations, determining the supply analysis of interest (characterization of tourism products) and demand (visitor profile and identifying of existing problems), this could be determined through surveys, interviews, institutional visits and FODA analysis, after we have obtained the corresponding results was established the strategic (strategic plan objectives, methodological process and strategy development process), once established it we proceeded to the philosophical formulation (vision, mission, values). Finally we prioritized the strategies and thereby worked in three programs and eight projects which to be projected from five to ten years for their development and implementation,